Unlocking The Potential of Artificial Intellignce: : A New Paradigm for Assessment in 21st Century Education - Ogunsakin, Isaac (International Journal of Research in STEM Education, 2024)
This systematic review explores the transformative role of artificial intelligence (AI) in shaping assessment practices within 21st-century education. It critically examines the integration of AI technologies such as Automated Essay Scoring (AES), adaptive learning systems, and learning analytics, emphasizing their contributions to personalized learning experiences and real-time feedback mechanisms. The review identifies key opportunities for AI to enhance educational assessment, including the automation of scoring and the provision of adaptive feedback. However, it also addresses significant ethical challenges such as algorithmic bias, data privacy, and the need for transparency. We urge policymakers and educators to establish robust ethical guidelines and invest in comprehensive educator training to ensure the responsible use of AI in educational settings. The future directions suggest an increase in the integration of AI technologies, emphasizing the need for ongoing research to enhance validity, reliability, and address ethical considerations in AI-driven assessment practices.